ANALISIS PENGARUH VIDEO ANIMASI TERHADAP HASIL BELAJAR IPA SISWA MADRASAH TSANAWIYAH - Mhd Rizky Fahrozy N Harahap; Palma Juanta; Shinta Marito Siagian; Jefri Banjarnahor (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
This research aims to analyze the effect of learning using animated videos on students' science learning outcomes. The research adopts a quantitative approach utilizing the T-Test statistical method with the SPSS (Statistical Product and Service Solutions) software version 22. Based on the analysis results, the mean scores for the pre-test in the experimental class and control class were 39.00 and 39.12, respectively, with significance values (sig 2-tailed) of 0.57 and 0.59. Therefore, it can be concluded that there is no significant difference in the average scores between the experimental and control classes in the pre-test. However, for the post-test results, the mean scores for the experimental class and control class were 70.00 and 43.21, respectively, with hypothesis testing results of 0.00 for both groups. This indicates a significant difference in average scores between the experimental and control classes in the post-test. This finding demonstrates that the use of animated video media in teaching significantly improves learning outcomes in the experimental class compared to the control class. The experimental class showed better attitudes and achievements in learning compared to the control class.